Ensaios sobre mobilidade internacional de capitais e crescimento econômico - Sergio Fornazier Meyrelles Filho (2009)
The subject matter of this work consists in a systematic inquiry about the possible effects of international capital mobility on the process of economic growth in different countries. Particularly, it aims to analyze if the prospects presented for the unrestricted opening to the capital movements result favourable to sustained growth, especially in the less developed economies. This study is composed of three essays presented in format of self-contained chapters even so interdependent. In the first chapter, we undertake a critical analysis of theoretical literature on the subject opposing the liberal arguments to the post-keynesian critical in defense of permanent capital control. In the following chapter, we stand out the centrality of aggregate demand ant therefore of the balance of payments for understanding the relation between international capital mobility and economic growth. We develop a theoretical model to study the relation between balance-of-payments constrained growth and capital controls, then formally introduced as an economic policy variable. This framework distinguishes between different kinds of capital flows and aims to establish a clear association between flows and stocks in analyzing the association among economic growth and external indebtedness. In the third chapter, these theoretical elements serve as an important reference for the proposed contribution to the empirical debate on capital mobility and growth. Such analysis is carried though the econometric estimation of a dynamic panel data model. The study observe information relative to a wide range of countries in different stages of its development, in the recent historical period. Finally, based on theoretical and empirical arguments we conclude in favor of capital controls as a fundamental component in the context of policies oriented through sustained economic growth in developing countries.